1998
DOI: 10.1002/(sici)1097-4628(19981017)70:3<507::aid-app12>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of suspensions with weakly interacting particles

Abstract: ABSTRACT:Rheological characterization of a model suspension containing hydroxylterminated polybutadiene and glass beads with filler concentration up to 30% by volume was performed by using a Haake parallel disk rheometer. The rheological tests conducted were the measurement of the storage modulus, GЈ, loss modulus, GЉ, and complex viscosity, *, as functions of the frequency and the steady shear viscosity as a function of the shear rate. The linear viscoelastic region was determined to extend up to 50% strain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A higher relaxation time indicates that the mean lifetime of the junction zones of xanthan is higher than that of zones formed by guar entanglements. In general, we observed that the G i values decreased with an increase in relaxation time (Table 4) for the same conditions of temperature and gum concentration, which is in agreement with the values obtained by Bayram et al (1998). The increase in relaxation time could be associated with the formation of intermolecular aggregates, which was facilitated by an increase in the polysaccharide concentration and the biopolymer characteristics.…”
Section: Dynamic Rheologysupporting
confidence: 89%
“…A higher relaxation time indicates that the mean lifetime of the junction zones of xanthan is higher than that of zones formed by guar entanglements. In general, we observed that the G i values decreased with an increase in relaxation time (Table 4) for the same conditions of temperature and gum concentration, which is in agreement with the values obtained by Bayram et al (1998). The increase in relaxation time could be associated with the formation of intermolecular aggregates, which was facilitated by an increase in the polysaccharide concentration and the biopolymer characteristics.…”
Section: Dynamic Rheologysupporting
confidence: 89%
“…(2) and (3) are both ineffective for such materials. Bayram et al (1998) showed the validity of the Cox-Merz rule for Newtonian suspensions up to a particle volume fraction of 30%, while Kaully et al (2007) showed its validity up to a particle volume fraction of 20-40%, depending on the particle size distribution. Both papers showed that for higher concentrations, the complex viscosity resulted smaller than the dynamic ones ( * < ), in contrast to the case of shear thinning suspensions.…”
Section: Introductionmentioning
confidence: 95%
“…In this study, the linear least squares method (19, 23,24) was used in order to obtain the relaxation time and the relaxation strength.…”
Section: Analysis Of Viscoelastic Propertiesmentioning
confidence: 99%
“…Another useful method of analysis is the calculation of the relaxation times distribution using oscillatory shear data (19)(20)(21)(22)(23)(24). The calculated relaxation strength-relaxation time distribution can then be used to determine parameters such as the zero shear rate viscosity, rubbery plateau and mean relaxation time providing information about the molecular structure of the blend.…”
Section: Introductionmentioning
confidence: 99%